Impact of chronic stress on cardiovascular system: Libyan conflict health perspective part 2: Mechanisms and treatment strategies - Elhwuegi, Abdalla; Teebar, Lamis (Libyan International Medical University Journal, 2018)
Recent studies have provided clear and convincing evidence that chronic stress contributes significantly to the pathogenesis and expression of cardiovascular diseases (CVDs). This bibliography is a systematic review on the impact of chronic stress on the cardiovascular system with a special reflection on the Libyan conflict. It is divided into two parts, Part 1 deals with types of chronic stresses, while Part 2 deals with mechanisms involved in chronic stress and their treatments. Medline/PubMed, Google Scholar, and Scopus databases were used to search for peer-reviewed papers dealing with the review theme. Mechanisms responsible for the development of chronic stress are either behavioral or biological. Behavioral factors include lifestyles (e.g., smoking, alcohol, and physical inactivity). Biological mechanisms include sympathetic overdrive, hypothalamic–pituitary–adrenal axis overactivity, and low activity of central gamma-aminobutyric acid. Chronic stress managements and treatment strategies include psychological treatment like cognitive behavioral interventions, breathing techniques like Yoga and/or pharmacological treatments like selective serotonin reuptake inhibitors, and drugs that inhibit sympathetic hyperactivity.
Keywords: Chronic stresses; mechanisms of chronic stresses; treatments of chronic stresses